Lifestyle modifications and control of cardiovascular risk factors in older adults with hypertension: from NHANES 1999–2018 - Ying Tang; Zhi Zhang; Xiaowei Liu (BMC Geriatrics)
Abstract Background Self-management of hypertension is particularly emphasized for older patients. Specifically, it is critical that initiatives regarding lifestyle modifications be applied to reduce the cardiovascular burden of hypertension among the elderly population. Methods We included participants aged 65 years or older with hypertension from the National Health and Nutrition Examination Survey (NHANES) years 1999–2018 to analyze the adherence to lifestyle recommendations and the control of cardiovascular risk factors. Recommended lifestyle behaviors and targets for cardiovascular risk factor controls were defined according to the clinical guidelines for the management of hypertension. Logistic regression analyses were utilized to identify factors associated with nonadherence. Results Of 10,162 participants (mean age, 74.45 years) included, 4350 (42.81%) had controlled blood pressure. Adherence to healthy lifestyle behaviors varied among respondents. Smoking cessation (88.82%) and alcohol reduction (74.11%) were relatively high, whereas adherence to physical activity (14.57%), low salt diet (36.81%), and fiber intake (12.87%) were significantly lower. A significant proportion of respondents achieved target levels for LDL-C (76.00%) and HbA1c (72.49%), whereas fewer participants met BMI (25.02%) and waist circumference (31.26%) goals for cardiovascular risk factor control. After multivariable adjustment, male gender (OR: 1.53 [1.09–2.17]), non-Hispanic black race (OR: 1.85 [1.06–3.24]), metabolic syndrome status (no vs. yes, OR: 0.67 [0.47–0.94]), and chronic kidney disease status (no vs. yes, OR: 0.63 [0.41–0.97]) were associated with increased odds of unhealthy lifestyle, whereas male gender (OR: 1.37 [1.04–1.80]), high socioeconomic status (OR: 1.61 [1.05–2.49]), metabolic syndrome status (no vs. yes, OR: 0.03 [0.02–0.04]), and diabetes mellitus status (no vs. yes, OR: 0.68 [0.49–0.96]) were associated with increased odds of uncontrolled cardiovascular risk. Conclusions Adherence to physical activity and healthy diet, and control of central obesity are suboptimal among older patients with hypertension. The etiology of nonadherence is multifactorial and includes causes associated with sociodemographic status, and comorbidities.